Crew competence and compliance as determinants of oil water separator effectiveness: implications for marine pollution prevention - Putu D. Darmawan; Alfret Luasunaung; Wilmy E. Pelle; Nickson J. Kawung; Leonardus R. Rengkung; Markus T. Lasut (AQUATIC SCIENCE & MANAGEMENT, 2026)
Marine pollution from oily bilge water discharges continues to pose a significant threat to ocean ecosystems and maritime environmental sustainability. The Oil Water Separator (OWS), mandated under MARPOL Annex I, serves as the primary onboard technological control to prevent such discharges; however, its operational effectiveness is contingent not solely upon equipment design but also upon human factors, particularly the competence and regulatory compliance of shipboard personnel. This study aims to examine the influence of crew competence and compliance on the effectiveness of OWS operations in mitigating marine pollution. A quantitative explanatory research design was employed, utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the hypothesized relationships. Data were collected via structured questionnaires administered to 60 engine officers serving across 15 commercial vessels calling at Bitung Port, North Sulawesi, Indonesia. The results reveal that crew competence exerts a significant positive effect on OWS effectiveness (β = 0.473; p = 0.022), while crew compliance demonstrates a stronger significant effect (β = 0.522; p = 0.007). Collectively, both constructs account for 56.7% of the variance in OWS effectiveness (R² = 0.567). These empirical findings underscore the critical need for targeted capacity-building initiatives to enhance technical competence and the reinforcement of strict adherence to operational protocols and environmental regulations. The study contributes practical insights for shipping companies, port state control authorities, and maritime policymakers in strengthening pollution prevention strategies and advancing sustainable shipping practices.